Two new endemic cave-living moths from Hawai‘i Island: a new species of Pseudoschrankia (Erebidae), and a new species of Mestolobes Crambidae) - Medeiros, Matthew J; Howarth, Francis G (Zootaxa, 2017)
Two new endemic Hawaiian Lepidoptera species are herein described; both are associated with caves. The new species, Pseudoschrankia nohoana sp. nov. and Mestolobes olali sp. nov., have been found exclusively in caves or cave entrances on the Big Island of Hawai‘i, although neither species appears to possess any specializations for living in caves.